A comparison of presence detection techniques for mote-based habitat monitoring - Talampas, Marc Caesar R. (2006)
This study compares different presence detection techniques for use in habitat monitoring systems. Five different presence detection systems were implemented and interfaced to MICA2 sensor nodes. Modified versions of the TinyOS application Surge_Reliable were used as the main software for data acquisition and communications. A bird cage with avian nest boxes served as the test environment for the presence detection systems. The accuracy, price, power, consumption, code complexity, and startup time of each sensor system were used as points of comparison.